Aktivitas Antibakteri Hand Sanitizer Berbahan Dasar Asap Cair Hasil Torefaksi Cangkang Kelapa Sawit Terhadap Bakteri Escherichia coli - Rosmainar, Lilis; -, Karelius; Toemon, Angeline Novia; Sulastri, Idam (Jurnal Farmasi Udayana; Vol. 11, No. 1, Tahun 2022DO - 10.24843/JFU.2022.v11.i01.p03, 2022)
Antibacterial activity of hand sanitizer based on liquid smoke from torrefaction of palm oil against Escherichia coli has been done. The liquid smoke produced from the oil palm shell torrefaction process has the potential to be used as an antiseptic base for hand sanitizer products. This is due to its high phenol and acetic acid content. Many other compounds must be separated from liquid smoke, one of the processes that can be separated with distillation. Compounds of liquid smoke from distillation are phenol, propanoic acid, 2-propanone, and acetic acid. This research was conducted by varying the concentration of liquid smoke in a hand sanitizer by 15%, 25%, and 35%. The results showed that the number of bacterial colonies at a concentration of 15% was 910,000 CFU/ml, 25% was 1,130,000 CFU/ml, and 35% was 1,140,000 CFU/ml. The effective concentration to kill bacteria is in hand sanitizer based on liquid smoke with a concentration of 15% was 57,59%.   Keywords : palm kernel shells, liquid smoke, Escherichia coli